Silk-tropoelastin protein films for nerve guidance - White, James D. (Acta Biomater, 2014)
Peripheral nerve regeneration may be enhanced through the use of biodegradable thin film biomaterials as highly tuned inner nerve conduit liners. Dorsal root ganglion neuron and Schwann cell responses were studied on protein films comprised of silk fibroin blended with recombinant human tropoelastin protein. Tropoelastin significantly improved neurite extension and enhanced Schwann cell process length and cell area, while the silk provided a robust biomaterial template. Silk-tropoelastin blends afforded a 2.4 fold increase in neurite extension, when compared to silk films coated with poly-d-lysine. When patterned by drying on grooved polydimethylsiloxane (3.5 µm groove width, 0.5 µm groove depth), these protein blends induced both neurite and Schwann cell process alignment. Neurons were functional as assessed using patch-clamping, and displayed action potentials similar to those cultured on poly(lysine)-coated glass. Taken together, silk-tropoelastin films offer useful biomaterial interfacial platforms for nerve cell control which can be considered for neurite guidance, disease models for neuropathies, and surgical peripheral nerve repairs.